Generation and Applications of Extra-Terrestrial Environments on Earth. - Beysens, Daniel A. (River Publishers, 2022)
This book has been prepared under the auspice of the European Low Gravity Research Association (ELGRA). The book covers ground-based research instruments and environments for both life and physical sciences research.